Adverse Selection in the Group Life Insurance Market - Timothy F. Harris; Aaron Yelowitz; Jeffery Talbert; Alison Davis (Institute of Labor Economics (IZA), 2022)
The employer-sponsored life insurance (ESLI) market is particularly susceptible to adverse selection due to community-rated premiums, guaranteed issue coverage, and the existence of a well-functioning individual market as a substitute. Using administrative payroll and healthcare claims data from a large university, we find evidence of adverse selection in the supplemental ESLI market. Employees in worse health, as measured by the Charlson's Comorbidity Index, are more likely to elect coverage than those in better health. Nonetheless, we also find that employees typically do not increase coverage following diagnosis of a severe illness even when they can without providing evidence of insurability. Furthermore, demand estimation shows that employees are not price-sensitive and that the estimated increases in premiums due to adverse selection are unlikely to cause significant welfare loss.
Keywords: D82; G22; J33; 330; adverse selection; employer-sponsored life insurance